PENGARUH PEER EDUCATION TERHADAP PERILAKU MEROKOK PADA REMAJA DI SMAN “X” DENPASAR - Ni Putu Sri Wiratini; Ni Luh Putu Eva Yanti; Anak Agung Ngurah Taruma Wijaya (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Smoking in adolescents currently increasing. The result of smoking in adolescents abuse cause addiction and trigger negative behaviour like alcohol usage, drugs, abuse and etc. One of prevention has been conducted by giving health education with peer education. Peer education is a peer adolescents support group with adolescents as fasilitator who qets education about smoking, communication technique, role play method and sharing experience with their members. This study aims to find out the effect of peer education toward smoking in adolescents. This study has been conducted by using pre-experimental design, that is one group pre-post test design. Sample consists of 60 students selected with probability sampling technique with systematic random sampling. The result of data analysis by using wilcoxon test and the result obtained that there is significant effect of peer education toward smoking in adolescents. The schools should to develop and apply this peer education as preventive of smoking in adolescents.